Analisis Pemahaman Konsep Matematika Siswa Kelas X SMAN 1 Jelimpo pada Materi Eksponen - Lestina Sanova; Sepriani Liliana (EduInovasi: Journal of Basic Educational Studies, 2026)
This study aims to analyze students’ understanding of mathematical concepts in exponent material for class X students at SMAN 1 Jelimpo. This research was motivated by the low understanding of students’ mathematical concepts, especially in exponent material. Based on observations during the PLP program, it was found that students still had difficulties understanding exponent concepts, restating concepts, and solving various types of problems. This study used a qualitative approach with descriptive research type. The research subjects were selected using purposive sampling technique based on high, medium, and low ability categories. Data collection techniques were carried out through tests and interviews. The research instruments consisted of conceptual understanding test questions and interview guidelines. Data validity was checked using technique triangulation. Data analysis techniques included data reduction, data presentation, and drawing conclusions. The results showed that students’ understanding of mathematical concepts in exponent material varied. Students with high ability were able to understand and apply exponent concepts well. Students with medium ability understood some concepts but still made mistakes in applying concepts to certain problems. Meanwhile, students with low ability still had difficulties understanding the basic concepts of exponents and solving the given problems. Based on the results of the study, it can be concluded that students’ understanding of mathematical concepts in exponent material still needs to be improved, especially in understanding basic concepts and applying concepts in solving mathematical problems.